Інженерний захист території Києво-Печерської лаври: історичний досвід, сучасний стан, проблеми і шляхи вирішення - Черевко, І.А.; Літвінчук, Д.В.; Головатенко, Ю.Г. (Сіверщина в історії України, 2024)
Стаття висвітлює комплексне дослідження формування систем інженерного захисту на території Національного заповідника «Києво-Печерська лавра» в період XVIII–XXI ст. На сьогодні споруди інженерного захисту минулого часу, як об’єкти культурної спадщини, становлять невід’ємну частину історичного ландшафту, вимагаючи особливих заходів щодо їх збереження. Розглянуто основні елементи системи інженерного захисту схилів від зсувів та підтоплень ґрунтовими водами пам’яток, розташованих на території Нижньої та Верхньої лаври: підпірні стінки, водостоки, променеві дренажі, дренажі мілкого та глибокого закладання, тощо; охарактеризовано їх недоліки та переваги. Здійснено аналіз сучасного стану інженерних мереж, окреслено загальну проблематику та головні чинники впливу. Оскільки подекуди ефективність та доцільність подальшої експлуатації цих споруд в сучасних умовах потребують переоцінки, виникає потреба вирішення новітніх проблем та викликів сьогодення, що постають перед суспільством у сфері збереження історичних ареалів. Розглянуто питання щодо модернізації існуючих і будівництва нових систем в умовах постійно зростаючого техногенного навантаження. The article highlights a complex study of the formation of engineering protection systems on the territory of the National Reserve «Kyiv-Pechersk Lavra» in the period of the XVIII–XXI centuries. To the buildings reinforcement and to prevent the development of landslides on the Lavra slopes, starting from the 17th century, retaining walls were erected, from small (2-4 m) to massive (5-16 m) in height. Today there are more than 5 km of retaining walls (brick, concrete, pilebased). It should be noted that in addition to maintaining the soil massif, retaining walls also obstruct groundwater, creating a barrage effect, which sometimes leads to concentrated flooding of monuments, in particular the Near Caves. In order to remove the support and drain groundwater, in the walls discharge holes were arranged, which made it possible to protect some labyrinths of the Near Caves from flooding. At the beginning of the 19th century in order to prevent the development of landslide processes, which were caused by the overwetting of the soil massif by underground and surface (infiltration) waters, the construction of drainage systems was already used. In particular, the 18-bis drainage system, built in 1810, gave stability to Dalnyopecherny Hill and protected the Far Caves from destruction. Mass construction of drainage systems on the Dnieper slopes started at the beginning of the 20th century. Initially, brick galleries with drainage holes were built; later they were replaced by drainage tunnel systems with drainage wells with wooden fastenings, which were replaced by concrete ones in the 1960s; since the 1970s, shallow drainages and drainage gallery systems have been built. The total length of the drains constructed and the territory of the Lavra exceeds 10,000 m. Since the 2010s, in order to protect buildings from flooding in the territory of the reserve, the construction of radial drainages of shallow laying (5-6 m), the total length of which is approx. 1500 m. Radial drainages are mainly intended for lowering the groundwater levels of shallow and temporary aquifers, which negatively affect the state of architectural monuments. Today, the effectiveness and expediency of further exploitation of these structures in modern conditions needs re-evaluation, there is a need to solve the latest problems and challenges of the present, which society faces in the field of preservation of historical sites.